A Coupled Novel Green Element and Embedded Discrete Fracture Model for Simulation of Fluid Flow in Fractured Reservoir. (5th July 2021) - Cheng, Linsong; Du, Xulin; Cao, Renyi; Wang, Zhikai; Shi, Junjie
Abstract : In this study, we present a hybrid model coupled with two-set nodes Green element method (GEM) and embedded discrete fracture model (EDFM) for capturing the effect of transient flow in inhomogeneous fractured porous media. GEM is an excellent advanced algorithm, which can solve nonlinear problems in heterogeneous media. That is also an obvious advantage of GEM against the original boundary element method (BEM). The novel GEM has double nodes of pressure and flux and it is an improvement of classical GEM, which has a second-order precision and fits for triangle structured grids. In the place of adopting the linear flow approximation for original EDFM, the interflows between local triangle matrix grids and fracture elements are derived using the novel GEM, which has higher accuracy than those in previous EDFMs. Consequently, the modified hybrid model can indeed calculate the pressure and flux distribution of transient flow in multifracture porous media. Three numerical cases are presented to show the practicability of our novel model which include (i) multistage fractured horizontal well, (ii) heterogeneous fractured porous media, and (iii) complex fracture networks (CFNs) in an unconventional reservoir.